PENENTUAN RUTE KENDARAAN MENGGUNAKAN METODE CLARK AND WRIGHT SAVING HEURISTIC (STUDI KASUS : PT. SINAR SOSRO) - Mariana Sianipar; David Fu’ani; Wahyudi Sutopo; Muhammad Hisjam (Performa: Media Ilmiah Teknik Industri, 2017)
Distribution and transportation are very vital for the company business beverages that must distribute its products to many areas of the consumer, for example is a bottled tea company.  A good distribution plan and an optimum route would decrease cost and time for distributing the products.  In a real case study for a bottled tea in Surakarta area, the fluctuating demand of consumers cannot be ensured and these mismatches by a salesman that should be based on the distribution plan and the realization of visit (RRK) resulted in the absence schedule. Therefore, it is required an optimum route to help the salesman in doing RRK or distribution without ignoring predetermined targets. There is a settlement solution will be more orderly preparation of these are using a Clark and Wright Saving Heuristic method. The method is able to assist the performance of salesmen and cost savings in the delivery of Surakarta area. In this paper, we have presented a real cases vehicle routing based on Clark-Wright algorithm to solve the open vehicle routing problem (OVRP) of bottled tea distribution in Surakarta District. We have modified the Clark Wright algorithm with three procedures composed of Clark and Wright formula. The methods of swap, 2 OPT and 3-OPT were used to improve our best solution in shortest route and the cheapest cost of distribution.